Cover Feature: The Role of [BF4]− and [B(CN)4]− Anions in the Ionothermal Synthesis of Chalcogenidometalates (Chem. Eur. J. 14/2018). Issue 14 (31st January 2018) - Santner, Silke; Sprenger, Jan A. P.; Finze, Maik; Dehnen, Stefanie
Abstract : The nature of the ionic liquid borate anion, [BF4 ] − or [B(CN)4 ] −, is an important parameter in the ionothermal synthesis of crystalline selenidostannates using K4 [SnSe4 ]⋅ 4 H2 O and K2 [SnCl6 ]. [BF4 ] − anions tend to form solid K[BF4 ], whereas the K + cations remain available for the syntheses in [B(CN)4 ] − ‐based ionic liquids. The choice of both the anion and the reaction temperature thus influences the product spectrum, and also indirectly the optical absorption properties of the uncommon salts like (C4 C1 C1 Im)5 [Sn9 Se20 ][BF4 ] or K2 [Sn3 Se7 ]. More information can be found in the Full Paper by S. Dehnen, et al. on page 3474 .